What is the best fixation technique for isolated talonavicular arthrodesis? – A systematic review. (March 2023) - Arumugam, Vinodh; Ranjit, Srinath; Patel, Shelain; Welck, Matthew
Abstract: Summary: Talonavicular arthrodesis is associated with a rate of non-union that ranges from 3 % to 37 %. Various fixation devices have been reported for talonavicular arthrodesis including screws, staples, plates, K-wires and intraosseous fix systems, however there is no definitive gold standard. This systematic review aims to compare clinical outcomes between different fixation devices for talonavicular arthrodesis. Methods: MEDLINE, EMBASE, CENTRAL and Google Scholar were reviewed for studies reporting on outcomes of different fixation techniques for talonavicular arthrodesis indicated for osteoarthritis, inflammatory and post-traumatic arthritis from 1946 to 2021. The primary outcome measure was union rate. Secondary outcome measures included functional improvement, cost, quality of life and patient satisfaction. Results: 9 articles involving 141 cases of talonavicular arthrodesis were identified. Fusion rates were as follows: screw fixation (n = 75): 87.5 % to 100 %, staple fixation (n = 13): 100 %, intraosseous fix system (n = 16): 100 %, and K-wire fixation (n = 2): 100 %. One study utilised a dorsal locking plate with two supplemented compression screws (n = 9, fusion rate= 100 %) and two studies used a combination of screws with staples (n = 26, fusion rate= 96 %). 7 of 9 studies measured functional outcomes and pain relief with improvement demonstrated in all fixation techniques. Quality of life, satisfaction and cost were inadequately reported amongst the included studies. All studies were rated as serious risk of bias. Conclusion: This systematic review consolidates the evidence for outcomes of different fixation techniques for TN arthrodesis, however a definitive judgement regarding the best fixation technique is unobtainable from current clinical evidence, due to lack of high-quality studies. With review of biomechanical studies and the limited clinical data, fixation with plate plus screw is most promising and would warrant further comparative study. Level of evidence: IV. Highlights: Various fixation devices have been reported for talonavicular arthrodesis, however there is no gold standard. 9 studies highlighted for review with high rates of union demonstrated regardless of fixation technique. All reviewed studies rated as serious risk for bias with small sample sizes and inconsistent methodology. Plate plus screw fixation is deemed most promising considering the limited clinical data and reviewed biomechanical studies.